2013
DOI: 10.1002/bmc.2953
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of anticancer drugs by capillary electrophoresis: a review

Abstract: Capillary electrophoresis is a fast, inexpensive and low detection limit technique for the analysis of anticancer drugs. It has been used to analyze various anticancer drugs in biological samples, pharmaceutical preparations and environmental matrices. It has also been used to detect various cancer biomarkers in cancer patients. The present article describes the state-of-the art of capillary electrophoresis for the analyses of anticancer drugs. Various drugs discussed belong to several groups such as antimitot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 91 publications
(138 reference statements)
0
25
0
Order By: Relevance
“…Diversities of cancer genetic abnormality and molecular malfunctions require different categories of anticancer drugs or even anticancer drug combinations [8–10]. Approximately 84 anticancer or anti-metastatic drugs have been licensed in the USA [25] and 178 anticancer drugs are clinically utilized as of 2013 worldwide [26]. Meanwhile, anticancer drugs are mechanically diversified and tailored to different types of tumor categories.…”
Section: Current Cancer Therapy Pg Routines and Future Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversities of cancer genetic abnormality and molecular malfunctions require different categories of anticancer drugs or even anticancer drug combinations [8–10]. Approximately 84 anticancer or anti-metastatic drugs have been licensed in the USA [25] and 178 anticancer drugs are clinically utilized as of 2013 worldwide [26]. Meanwhile, anticancer drugs are mechanically diversified and tailored to different types of tumor categories.…”
Section: Current Cancer Therapy Pg Routines and Future Trendsmentioning
confidence: 99%
“…In spite of these utilizations, PG is not very useful for choosing the most suitable anticancer drugs from the large anticancer drug arsenal (≈84 anticancer agents or drugs licensed in the USA) [25] and 178 anticancer drugs licensed worldwide [26] (let alone huge numbers of drug combination possibilities). Long before, it has been found that drug combinations can commonly increase therapeutic efficacies and outcome in clinical cancer trials.…”
Section: Dilemma For Anticancer Therapy Pgmentioning
confidence: 99%
“…Various biological molecules (bioinformatics) have been widely reported to have diagnostic, prognostic and/or therapeutic predictive values in cancer patients [5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21]. Before initiating antibody therapy (treatment with monoclonal antibodies or polyclonal antibodies) or other type of targeted anticancer drug or biotherapies, [22] it is ideal Since cancer is a genetic disease, finally improvements of our knowledge about human cancer genomes by next generations of sequencing (NGS) [26] are urgently needed.…”
Section: Panorama Of Cancer Bioinformatics In Personalized Cancer Thementioning
confidence: 99%
“…
to know the levels of their targeted antigens or receptors in tumors in order to provide a rational basis for the quality of anticancer treatments [5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21]. Besides, since the cancer tissue bioinformatics detection methodologies can be varied greatly, bioinformatics technical studies for pinpointing oncogenic status are also an interesting topic presently and in future.

Bioinformatics methods are high throughput assays for identifying the original and causative cancer biomarkers in personalized chemotherapy [9].

…”
mentioning
confidence: 99%
“…So simultaneous determination of the concentration levels of vinca alkaloids in raw C. roseus and human serum samples is urgently needed for the use of drug with strict monitoring. In recent years, various analytical methods for determination of these vinca alkaloids in C. roseus and human serum had been reported [10][11][12][13][14][15][16][17][18][19][20]. Among these available methods, high performance liquid chromatography (HPLC) coupled with diode array detector (DAD), fluorescence detector (FLD) and mass spectrometry (MS) were the most widely used methods than other analytical strategies (e.g.…”
Section: Introductionmentioning
confidence: 99%